2013
DOI: 10.1158/1055-9965.epi-12-1351
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Risk of Colon Cancer Due to Cigarette Smoking May Be Greater in Women than Men

Abstract: Background: Smoking is a recently established risk factor for colon cancer. We wanted to explore the hypothesis that women may be more susceptible to smoking-attributed colon cancer than men as one of the possible explanations for the high colon cancer risk of Norwegian women.Methods: We followed 602,242 participants aged 19 to 67 years at enrollment in 1972-2003, by linkage to national registries through December 2007. We used Cox proportional hazard models to estimate HRs and 95% confidence intervals (CI).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 28 publications
7
35
1
Order By: Relevance
“…In the present report, the association between cigarette smoking and rectal cancer was similar for men and women. Previously, we reported from the same cohort that smoking increased the risk of colon cancer to a greater extent for women than men [2]. Our present findings of no difference between the gender in the smoking related increased risk of rectal cancer are in accordance with three [17-19] smaller Japanese cohort studies including 200 cases of rectal cancer [19] or less [17,18].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present report, the association between cigarette smoking and rectal cancer was similar for men and women. Previously, we reported from the same cohort that smoking increased the risk of colon cancer to a greater extent for women than men [2]. Our present findings of no difference between the gender in the smoking related increased risk of rectal cancer are in accordance with three [17-19] smaller Japanese cohort studies including 200 cases of rectal cancer [19] or less [17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, stronger relative risk among ever smokers for proximal compared to distal colon cancer has been documented [1]. In our previous study [2], we found that the smoking-related risk of colon cancer was more pronounced in the proximal part of colon for women, but not for men. For the distal part of colon, we could not demonstrate a difference by gender.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Given that even with smoking cessation CRP levels remain increased over 19 years ( 31 ), and that CRP levels in childhood predict CRP in adulthood ( 32 ), our novel fi nding of a predominant effect of smoking on hs-CRP levels in girls not using OCs is important in this context. It has been reported that smoking exposure is more harmful to health in women than in men, e.g., female smokers were more vulnerable to colon cancer than male smokers ( 33 ), and smoking in women was associated with 25% greater coronary heart disease risk compared with smoking in men ( 34 ). In line with these reports and the present study, we have previously shown in this adolescent population that long-term passive smoking exposure was associated with lower levels of HDL-cholesterol in 17-year-old girls but not boys ( 35 ).…”
Section: Resultsmentioning
confidence: 99%